Electrically controlled spin-switch and evolution of Hanle spin precession in graphene. (13th June 2019) - Zhao, Bing; Khokhriakov, Dmitrii; Karpiak, Bogdan; Hoque, Anamul Md; Xu, Lei; Shen, Lei; Feng, Yuan Ping; Xu, Xiaoguang; Jiang, Yong; Dash, Saroj P
Abstract: Next generation of spintronic devices aims to utilize the spin-polarized current injection and transport to control the magnetization dynamics in the spin logic and memory technology. However, the detailed evolution process of the frequently observed bias current-induced sign change phenomenon of the spin polarization has not been examined in details and the underlying microscopic mechanism is not well understood. Here, we report the observation of a systematic evolution of the sign change process of Hanle spin precession signal in the graphene nonlocal spintronic devices at room temperature. By tuning the interface tunnel resistances of the ferromagnetic contacts to graphene, different transformation processes of Hanle spin precession signal are probed in a controlled manner by tuning the injection bias current/voltage. Detailed analysis and first-principles calculations indicate a possible magnetic proximity and the energy dependent electronic structure of the ferromagnet-graphene interface can be responsible for the sign change process of the spin signal and open a new perspective to realize a spin-switch at very low bias-current or voltage.